Early Childhood Digital Literacy Strategies and Approaches: A Systematic Review PRISMA with Watase Uake Web Use - Didik Suryadi; Partikasari, Rika; Julie Simon Macariola (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
The incorporation of digital media into early literacy learning is the main emphasis of this research, which examines digital literacy methods and techniques for improving children's early reading abilities. The study examined Scopus-indexed papers released between 2015 and 2025, utilizing a methodical literature review based on the PRISMA 2020 framework, and used the Watase Uwake tool to evaluate the use of digital literacy in early childhood education. Eight of the 133 identified articles satisfied the inclusion criteria for comprehensive analysis. According to the results, interactive digital media like augmented reality, digital storytelling, and instructional apps greatly aids in the early childhood development of reading comprehension, vocabulary, and phonological awareness. But the success of these digital interventions depends heavily on teachers' willingness to incorporate technology into the curriculum and on parents' active role in directing their children's digital experiences. In particular, there are research gaps pertaining to the roles of parental support and teacher readiness, particularly in the Indonesian setting. This study offers fresh perspectives on the integration of digital literacy into early reading instruction and emphasizes the need for cooperation between educators, parents, and legislators in order to create a positive learning environment. In order to guarantee the successful integration of technology into early childhood education both in Indonesia and throughout the world, the practical implications highlight the need for focused teacher training programs to improve their digital literacy. To get the most out of digital literacy for early reading development, these results highlight the necessity of a comprehensive strategy that includes all parties